1997
DOI: 10.1097/00000539-199707000-00017
|View full text |Cite
|
Sign up to set email alerts
|

Thromboelastographic Changes in Healthy Parturients and Postpartum Women

Abstract: Thromboelastography (TEG) using disposable plastic cups and pins was performed with native whole blood (native group) in 17 nonpregnant volunteers, 134 healthy term pregnant women (>36 wk gestation), and 69 postpartum women. Thromboelastography was also performed with celite-activated whole blood (celite group) in 15 nonpregnant female volunteers, 38 healthy term pregnant women, and 34 postpartum women. The thromboelastographic parameters r and K were significantly decreased in pregnant and postpartum women co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
72
1
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(82 citation statements)
references
References 14 publications
8
72
1
1
Order By: Relevance
“…12 Sharma et al used the thromboelastograph to show that the hypercoagulable changes associated with pregnancy were present until 12-24 h postpartum. 13 Steer et al performed a study involving standard thromboelastography with 41 women at the end of pregnancy and reported a decrease in clotting time suggesting coagulation is acti- vated in pregnancy whereas other studies have suggested a hyperactivation (enhanced initiation of coagulation) of coagulation in pregnancy based on high levels of coagulation activation markers (prothrombin fragments F1+2 and thrombin-antithrombin complexes) found in maternal blood. [14][15][16] In agreement with Steer et al our results suggest that in pregnancy the initiation of clotting, thrombin formation and start of clot polymerisation is increased as well as the response of the coagulation process once it has been initiated (as demonstrated by lower CFT-INTEM Ò and CFT-EXTEM Ò values found during pregnancy).…”
Section: Discussionmentioning
confidence: 99%
“…12 Sharma et al used the thromboelastograph to show that the hypercoagulable changes associated with pregnancy were present until 12-24 h postpartum. 13 Steer et al performed a study involving standard thromboelastography with 41 women at the end of pregnancy and reported a decrease in clotting time suggesting coagulation is acti- vated in pregnancy whereas other studies have suggested a hyperactivation (enhanced initiation of coagulation) of coagulation in pregnancy based on high levels of coagulation activation markers (prothrombin fragments F1+2 and thrombin-antithrombin complexes) found in maternal blood. [14][15][16] In agreement with Steer et al our results suggest that in pregnancy the initiation of clotting, thrombin formation and start of clot polymerisation is increased as well as the response of the coagulation process once it has been initiated (as demonstrated by lower CFT-INTEM Ò and CFT-EXTEM Ò values found during pregnancy).…”
Section: Discussionmentioning
confidence: 99%
“…The hypercoagulable state of pregnancy has been clearly demonstrated by TEG, [24][25][26] and CS further promotes this thrombotic tendency. [1][2][3] However there are limited data assessing TEG changes during the perioperative CS period.…”
Section: Discussionmentioning
confidence: 99%
“…Celite-induced factor XII activation accelerates thrombin formation, leading to more rapid assessment of coagulation status. Sharma et al [7] reported an up to fourfold reduction in R time, and an up to 73% increase in α angle when celite-activated TEG was compared with native TEG in pregnant women. Yamakage et al [8] also reported that celite-activated TEG resulted in an approximately 50% reduction in R time and a 19% increase in MA when compared with native TEG.…”
Section: Discussionmentioning
confidence: 98%
“…Clinically, TEG was shown to be effective in guiding transfusion therapy in the early days of liver transplantation [2]. Further modifications of TEG, including celite activation and heparinase, have been introduced, making TEG a "point-of-care" coagulation monitor in a wide variety of surgical procedures [3][4][5][6][7]. At our institution, TEG with celite activation is performed in the operating room by anesthesiologists.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation